(3EeJGY GdCSeGY HeG ddQShd ef GdGHfGA hGdCMhGd hGdMaOI hGdeJGYs - (3CMeO Hf Ydj Hf YHO GdbGOQ, CHh GdYHGS GdMSjfj GdYHjOj, Jbj GdOjf GdebQjRj,J (B845 (3g` s
(3ChdgG (B:s
(3hHYO hcGf dg ef GdGehQ GdPGJjI hGdYQVjI dGZfG def UObI hGef Hg Yf eYQaJg s
(3BNQgG (B:s
(3hGeG QbJg hQMeJg hdWagYf CfS bGd cGf GdfHi Udi Gddg Ydjg hSde GPG GJi HGdTF jbhd GPgHhG Hg Edi adGfI aEfgG cGfJ UOjbI NOjLI GPgHhG Hg Edi HjJ adGfI aEfgG cGfJ JMH NOjLI hbGd GdhGbOi s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdChds
(3fSNI JJCda ef SJI CLRGA ai JSYI eLdOGJs
(3eUhQI Yf fSNI chHQjdi (B104 (3fSN SfI (B968s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B11s
(3HQhcdeGf (B- (3GdLRA (B3 - (3U (B39 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B32 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs